Median Lethal Concentration of Zanthoxylum rhetsa seed extracts on Grass carp Fingerlings (Ctenopharyngodon idella) (Valenciennes, 1844) in Captive Condition - Jomang, Olik; Behera, S.; Bhakta, Dibakar; Baksi, Snigdha; Saha, Shibam (Fishery Technology, 2020)
The bark extracts of the plant Zanthoxylum rhetsahave been widely used by people of ArunachalPradesh as a mean of catching fish. Therefore, themedian lethal concentration (LC50) value of Zanthoxylumrhetsa bark extracts on grass carp(Ctenopharyngodon idella) (Valenciennes, 1844) hasbeen determined in the present study. The seeds ofZ. rhetsa were collected from the forest of Tarakvillage, located in the Siang district of ArunachalPradesh and the toxicity test was conducted in thecontrol condition. Five different concentrations ofthe extract viz., 25 mg l-1, 35 mg l-1, 45 mg l-1,55 mg l-1 and 65 mg l-1 were prepared by addingthe extracts proportionately to the water. The LC50value of Z. rhetsa against C. idella was hosted as 45mg l-1 for 96 h exposure period. Toxicity of aqueoussolution of Z. rhetsa against fingerlings of grass carpwas found to be time and dose-dependent. It wasfound that there was a significant (p